Digital ethics, cultural values, and self-regulation of social media activities in Indonesia and Malaysia - Anom, Erman; Rassanjani, Saddam (Frontiers in Communication, 2026)
The rapid expansion of social media in Indonesia and Malaysia has generated new ethical challenges that dominant digital ethics and self-regulation frameworks, grounded mainly in Western individualistic assumptions, cannot adequately explain. While existing studies focus on legal regulation, digital literacy, or normative prescriptions, they rarely examine how cultural values shape individual self-regulation in non-Western digital contexts. This study addresses this gap by critically analysing the relationships between digital ethics, cultural values, and self-regulation in social media practices in Indonesia and Malaysia. Drawing on a structured narrative literature review and thematic analysis of recent scholarly sources, the study demonstrates that digital ethical behaviour in both countries is deeply embedded in collectivist norms, religious morality, and culturally specific mechanisms such as shame, social harmony, and communal accountability. Based on this analysis, the article proposes a novel conceptual framework—Contextual Digital Self-Regulation—which conceptualises ethical digital behaviour as emerging from the interaction of three interconnected layers: the individual layer (moral reflection and personal agency), the social layer (culturally embedded norms and collective expectations), and the structural layer (policy frameworks, educational systems, and platform architectures). The study advances existing digital ethics and self-regulation theories by offering a culturally grounded, non-Western perspective that challenges Universalist and individual-centred models. The findings highlight the importance of developing digital ethics education and governance frameworks that are context-sensitive and rooted in local value systems, particularly in Southeast Asian societies.